Effect of Low-Temperature Plasma Activated Water with Different Treatment Times on Myofibrillar Proteins of Thawed Pork - Manting Du; Fangge Hao; Shunyang Sun; Ke Li; Qisen Xiang; Junguang Li; Lichuang Cao; Yanhong Bai (Foods)
In this study, myofibrillar proteins (MPs) of thawed pork were treated with plasma-activated water (PAW) generated at different times (0, 5, 10, 15, 20, and 25 s) to investigate whether the function of MPs is improved through PAW and the corresponding regulatory mechanism. The results found that PAW treatments increased the surface hydrophobicity and altered the secondary and tertiary structure of MPs. The α-helix content of MPs treated by PAW reduced from 37.3% to 31.25%. In the PAW25s group, the oxidation of MPs was significantly raised, reflected by the higher carbonyl content and lower total sulfhydryl content compared with other groups (p < 0.05). Furthermore, PAW treatments increased the whiteness and improved the strength, immobilized water contents, resilience, chewiness, and adhesiveness of MP gels. The observation of intermolecular forces and microstructure of MP gels presented an increase in ionic bonding, disulfide bonding, and hydrophobic interactions but a decrease in hydrogen bonding in MP gels with PAW treatments, leading to more homogeneous and denser gel structures compared with the control group. In conclusion, PAW, with a short generation time, significantly fixed and enhanced the function of MPs extracted from thawed pork and, to some extent, improved the processing quality of the MPs of thawed pork.